2022
DOI: 10.3390/vaccines10010092
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of Standard and Double Doses of Hepatitis B Vaccine in Children after Liver Transplantation: An Open-Label, Randomised Controlled Trial

Abstract: A high prevalence of hepatitis B (HepB) antibody loss after liver transplantation (LT) and de novo HepB infection (DNH) was documented, hence revaccination to prevent DNH is crucial. This study aimed to compare the safety and immunogenicity of two HepB vaccine regimens in liver-transplanted children. Liver-transplanted children who were previously immunised but showed HepB surface antibodies (anti-HBs) ≤ 100 mIU/mL were randomised to receive a standard three-dose (SD) and double three-dose (DD) vaccine intramu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The immune response to vaccination in LT children might be more rigorous than in LT adults because of many factors, such as their younger age (20) and less comorbidity (21). Previous research on hepatitis B revaccination in LT children demonstrated a good response and slow-waning immunity, which differed from adult studies (27) and could explain why the immune response in LT children and adults could not be comparable. Hence, it is important to consider a specific study in the child population rather than generalizing the vaccination regimen based on adult data.…”
Section: Discussionmentioning
confidence: 97%
“…The immune response to vaccination in LT children might be more rigorous than in LT adults because of many factors, such as their younger age (20) and less comorbidity (21). Previous research on hepatitis B revaccination in LT children demonstrated a good response and slow-waning immunity, which differed from adult studies (27) and could explain why the immune response in LT children and adults could not be comparable. Hence, it is important to consider a specific study in the child population rather than generalizing the vaccination regimen based on adult data.…”
Section: Discussionmentioning
confidence: 97%
“…The last category included studies aiming at different immunization procedures. Jilg et al [14], Goldfarb et al [26], Sintusek et al [27], and Greenberg et al [28] studied the difference in the HBsAb positivity rate according to varying vaccination times (0, 1, 6; 0, 1, 12; 2, 4, 6 months) and varying dosages (5, 10, and 20 μg immunization). Taking the above factors into account, it could be reasonably explained that the positivity rate of HBsAb in the current study was higher than that in previous studies.…”
Section: Discussionmentioning
confidence: 99%